Local government expenditure in the Lublin voivodeship in 2010-2018 - Kobiałka, Anna (Wydatki gmin województwa lubelskiego w latach 2010-2018, 2020)
‘Gmina’ (i.e. a commune, a principal unit of administrative division in Poland) is required to perform specific tasks and incur expenditure related to its performance. Therefore, local government authorities must make decisions about the level and purpose of local expenditure. A particularly significant determinant of local development policy is expenditure on financing infrastructure investment. This paper aims to analyse and evaluate the expenditure level of ‘gminas’ located in Lublin voivodeship in 2010-2018. The analysis is based on a review of the dynamics of expenditure, its structure and level as well as changes in expenditure per capita. An area of special interest is the property investment expenditure of local government units. Communes in the Lublin voivodeship, similarly to those in the rest of Poland, have an increased amount of funds allocated to the performance of their tasks. A continuing increase in property expenditure can be observed, especially in the rural communes in the Lublin voivodeship, which is closely linked to the use of EU structural funds
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 103-114